Multilayer ceramic capacitor and method of manufacturing same
By adopting a glass composition with a double-layer structure and a conductive metal layer in the outer electrode of the multilayer ceramic capacitor, the shortcomings of the multilayer ceramic capacitor in the prior art in terms of high reliability and moisture resistance are solved, and higher capacitor reliability and moisture resistance are achieved.
Patent Information
- Application Number
- CN202410306708.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-27
- Filing Date
- 2024-03-18
- Publication Date
- 2025-04-29
AI Technical Summary
Existing multilayer ceramic capacitors have shortcomings in high reliability and moisture resistance, especially in ultra-small and ultra-high capacitance applications, which are difficult to meet the demand for high reliability.
By using a double-layer structure in the outer electrode of the multi-layer ceramic capacitor, the lower layer consists of a first glass containing aluminum, the upper layer consists of a second glass containing aluminum, and a conductive metal layer is formed during the sintering process to improve the contactability, corrosion resistance and moisture resistance of the outer electrode.
The excellent reliability and moisture resistance of multi-layer ceramic capacitors are achieved, and their application performance in high-demand fields are improved.
Smart Images

Figure CN119905347A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a multilayer ceramic capacitor and a method of manufacturing the same. Background Art
[0002] As ceramic electronic components using ceramic materials, there are capacitors, inductors, piezoelectric elements, varistors, thermistors, etc. Among ceramic electronic components, multilayer ceramic capacitors (MLCCs) are used in various electronic devices due to advantages such as small size, high capacitance, and easy mounting.
[0003] For example, a multilayer ceramic capacitor may be a chip capacitor mounted on a printed circuit board of various electronic products (such as an image device (e.g., a liquid crystal display (LCD), a plasma display panel (PDP), etc.), a computer, a personal portable terminal, a smart phone, etc.) for charging or discharging the same.
[0004] Recently, with the miniaturization of electronic products, multilayer ceramic capacitors are also required to be miniaturized and have ultra-high capacitance. To this end, the thickness of the dielectric layer and the inner electrode layer is reduced, and a multilayer ceramic capacitor having a structure in which a larger number of dielectric layers and inner electrode layers are stacked is being developed. Recently, these ultra-small and ultra-high capacitance multilayer ceramic capacitors are used in fields requiring a high level of reliability (such as electric vehicles), and therefore, such multilayer ceramic capacitors are required to have high reliability. Summary of the invention
[0005] Embodiments are directed to providing a multilayer ceramic capacitor having excellent reliability.
[0006] Another embodiment seeks to provide a method of manufacturing a multilayer ceramic capacitor.
[0007] A multilayer ceramic capacitor may include: a capacitor body including a dielectric layer and an inner electrode layer; and an outer electrode disposed outside the capacitor body, wherein the outer electrode includes a lower layer and an upper layer, the lower layer being located on a surface of the capacitor body to be electrically connected to the inner electrode layer, and the upper layer covering the lower layer, wherein the lower layer includes a first glass, the first glass may include aluminum (Al) in an amount greater than 0 atomic % and less than or equal to 8 atomic % relative to the total amount of components of the first glass, and wherein the upper layer includes a second glass, the second glass may include aluminum (Al) in an amount greater than or equal to 10 atomic % and less than or equal to 20 atomic % relative to the total amount of components of the second glass.
[0008] An atomic ratio of an amount of aluminum (Al) included in the second glass to an amount of aluminum (Al) included in the first glass may be greater than 2 and 100 or less.
[0009] The second glass may further include lithium (Li), sodium (Na), iron (Fe), barium (Ba), calcium (Ca), zinc (Zn), boron (B), silicon (Si), tin (Sn), or a combination thereof.
[0010] The second glass may include silicon (Si), and a total composition of aluminum (Al) and silicon (Si) is 20 atomic % to 50 atomic % with respect to a total composition of the second glass.
[0011] The first glass may further include lithium (Li), sodium (Na), iron (Fe), barium (Ba), calcium (Ca), zinc (Zn), boron (B), silicon (Si), tin (Sn), or a combination thereof.
[0012] The first glass may include barium (Ba) and zinc (Zn), and a total composition of the barium (Ba) and the zinc (Zn) is 50 atomic % to 95 atomic % with respect to a total composition of the first glass.
[0013] The first glass and the second glass may further include sodium (Na), and an atomic ratio of an amount of sodium (Na) included in the second glass to an amount of sodium (Na) included in the first glass may be greater than 2 and equal to or less than 100.
[0014] The first glass and the second glass may further include iron (Fe), and an atomic ratio of an amount of iron (Fe) included in the second glass to an amount of iron (Fe) included in the first glass may be greater than 2 and equal to or less than 100.
[0015] At least one of the lower layer and the upper layer may further include a conductive metal.
[0016] The conductive metal may include copper (Cu), nickel (Ni), silver (Ag), palladium (Pd), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), lead (Pb), alloys thereof, or combinations thereof.
[0017] The external electrode may include a central portion and a corner portion, the central portion including a central point of the multilayer ceramic capacitor in a thickness direction, the corner portion including a corner point of the multilayer ceramic capacitor, and a thickness ratio of the corner portion to the central portion of the external electrode may be 0.1 to 0.5.
[0018] The second glass may include lithium (Li).
[0019] The first glass may further include lithium (Li), and an atomic ratio of an amount of lithium (Li) included in the second glass to an amount of lithium (Li) included in the first glass is greater than 1.
[0020] A method for manufacturing a multilayer ceramic capacitor may include: applying a first paste for forming a lower layer of an external electrode on a surface of a capacitor body, the capacitor body including a dielectric layer and an internal electrode layer, the lower layer including a first glass; forming the lower layer by sintering the first paste; applying a second paste for forming an upper layer of the external electrode on the lower layer of the external electrode, the upper layer including a second glass; and forming the upper layer by sintering the second paste, wherein the first paste includes a first glass composition for forming the first glass, and the first glass composition may include an amount of aluminum oxide (Al2O3) greater than 0 mole parts and less than or equal to 8 mole parts relative to the total amount of the first glass composition of 100 mole parts, and wherein the second paste includes a second glass composition for forming the second glass, and the second glass composition may include an amount of aluminum oxide (Al2O3) greater than or equal to 10 mole parts and less than or equal to 20 mole parts relative to the total amount of the second glass composition of 100 mole parts.
[0021] A method for manufacturing a multilayer ceramic capacitor may include: applying a first paste for forming a lower layer of an external electrode on a surface of a capacitor body, the capacitor body including a dielectric layer and an internal electrode layer, the lower layer including a first glass; applying a second paste for forming an upper layer of the external electrode on the first paste, the upper layer including a second glass; and forming the external electrode including the lower layer and the upper layer by sintering the capacitor body coated with the first paste and the second paste, wherein the first paste includes a first glass composition for forming the first glass, and the first glass composition may include an amount of aluminum oxide (Al2O3) greater than 0 mole parts and less than or equal to 8 mole parts relative to a total amount of 100 mole parts of the first glass composition, and wherein the second paste includes a second glass composition for forming the second glass, and the second glass composition may include an amount of aluminum oxide (Al2O3) greater than or equal to 10 mole parts and less than or equal to 20 mole parts relative to a total amount of 100 mole parts of the second glass composition.
[0022] The first glass composition may further include barium oxide (BaO), calcium oxide (CaO), zinc oxide (ZnO), boron oxide (B2O3), silicon dioxide (SiO2), or a combination thereof.
[0023] Relative to 100 mol parts of the total amount of the first glass composition, the amount of barium oxide (BaO) can be 10 mol parts to 40 mol parts; the amount of calcium oxide (CaO) can be 1 mol parts to 20 mol parts; the amount of zinc oxide (ZnO) can be 10 mol parts to 40 mol parts; the amount of boron oxide (B2O3) can be 10 mol parts to 40 mol parts; and the amount of silicon dioxide (SiO2) can be 1 mol parts to 20 mol parts.
[0024] The second glass composition may further include lithium oxide (Li2O), sodium oxide (Na2O), barium oxide (BaO), calcium oxide (CaO), zinc oxide (ZnO), boron oxide (B2O3), silicon dioxide (SiO2), iron oxide (Fe2O3), or a combination thereof.
[0025] Relative to 100 mol parts of the total amount of the second glass composition, the amount of lithium oxide (Li2O) may be 1 mol part to 20 mol parts; the amount of sodium oxide (Na2O) may be 1 mol part to 20 mol parts; the amount of barium oxide (BaO) may be 10 mol parts to 40 mol parts; the amount of calcium oxide (CaO) may be 1 mol part to 20 mol parts; the amount of zinc oxide (ZnO) may be 1 mol part to 20 mol parts; the amount of boron oxide (B2O3) may be 10 mol parts to 40 mol parts; the amount of silicon dioxide (SiO2) may be 1 mol part to 20 mol parts; and the amount of iron oxide (Fe2O3) may be 0.1 mol part to 10 mol parts.
[0026] At least one of the first paste and the second paste may further include a conductive metal.
[0027] The multilayer ceramic capacitor according to the embodiment may have improved reliability by including an external electrode exhibiting excellent contact with an internal electrode layer, excellent corrosion resistance, and excellent moisture resistance reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a perspective view showing a multilayer ceramic capacitor according to an embodiment.
[0029] Figure 2 is along Figure 1 A cross-sectional view of a multilayer ceramic capacitor taken along line II' in FIG.
[0030] Figure 3 is along Figure 1 A cross-sectional view of a multilayer ceramic capacitor taken along line II-II' in FIG.
[0031] Figure 4 is a schematic diagram showing external electrodes of a multilayer ceramic capacitor according to an embodiment.
[0032] Figure 5 is a SEM analysis image of the external electrodes of the multilayer ceramic capacitor according to Example 1.
[0033] Fig. 6A is a cross-sectional SEM-EDS analysis image about the upper layer of the outer electrode according to Example 1.
[0034] Figure 6Bis a cross-sectional SEM-EDS analysis image about the lower layer of the outer electrode according to Example 1.
[0035] Fig. 7A is a cross-sectional SEM-EDS analysis image of an external electrode of the multilayer ceramic capacitor according to Example 1.
[0036] Figure 7B is a cross-sectional SEM-EDS analysis image of an outer electrode of the multilayer ceramic capacitor according to Comparative Example 1.
[0037] Figure 8 is a cross-sectional EPMA analysis image of an external electrode of the multilayer ceramic capacitor according to Example 1.
[0038] Fig. 9A is a graph showing the moisture resistance reliability regarding the external electrode according to Example 1.
[0039] Fig. 9B is a graph showing the moisture resistance reliability of the external electrode according to Comparative Example 1. DETAILED DESCRIPTION
[0040] Hereinafter, the present disclosure will be described in detail with reference to the accompanying drawings, in which embodiments of the present disclosure are shown. The accompanying drawings and description are to be considered illustrative rather than restrictive in nature. Throughout the specification, the same reference numerals represent the same elements. In the accompanying drawings, some components are enlarged, omitted or schematically shown, and the size of each component does not fully reflect the actual size.
[0041] The drawings are intended only to facilitate understanding of the exemplary embodiments disclosed in this specification, and it should be understood that the technical concepts disclosed herein are not limited to the drawings and include all modifications, equivalents or alternatives within the scope of the concepts and technologies of the present disclosure.
[0042] Although the terms "first", "second", etc. are used to explain each component, the components are not limited by such terms. These terms are only used to distinguish one component from another component.
[0043] Additionally, it should be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element, or intervening elements may also be present. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements. Furthermore, when an element is referred to as being "on" or "above" a reference element, it can be located above or below the reference element, and is not necessarily referred to as being "on" or "above" in a direction opposite to gravity.
[0044] Throughout the specification, the term "includes" or "has" is intended to specify the presence of the features, quantities, steps, operations, components, ingredients, or combinations thereof, but does not exclude the presence or addition of one or more other features, quantities, steps, operations, components, ingredients, and / or combinations thereof. Therefore, unless explicitly described to the contrary, the word "includes" and variations such as "comprising" or "having" will be understood to imply the inclusion of the stated elements but not the exclusion of any other elements.
[0045] Furthermore, throughout the specification, the phrase “in a plan view” or “on a plane” means observing a target portion from the top, and the phrase “in a cross-sectional view” or “on a cross section” means observing a cross section formed by vertically cutting the target portion from the side.
[0046] Throughout the specification, the term "connected" not only means that two or more constituent components are directly connected, but also may mean: two or more constituent components are indirectly connected through another constituent component; two or more constituent components are electrically connected as well as physically connected; or two or more constituent components are represented by different names but are combined together by position or function.
[0047] In the following, reference will be made to Figures 1 to 4 A multilayer ceramic capacitor according to an embodiment is described.
[0048] Figure 1 is a perspective view showing a multilayer ceramic capacitor according to an embodiment. Figure 2 is along Figure 1 A cross-sectional view of a multilayer ceramic capacitor taken along line II' in FIG. Figure 3 is along Figure 1 A cross-sectional view of a multilayer ceramic capacitor taken along line II-II' in FIG. Figure 4 is a schematic diagram showing external electrodes of a multilayer ceramic capacitor according to an embodiment.
[0049] Figures 1 to 3The L axis, W axis and T axis shown in represent the length direction, width direction and thickness direction of the capacitor body 110, respectively. Here, the thickness direction (T axis direction) can be a direction perpendicular to the wide surface (main surface) of the sheet component, and can be used as the same concept as the stacking direction of the stacked dielectric layer 111, for example. The length direction (L axis direction) can be a direction extending parallel to the wide surface (main surface) of the sheet component, and can be approximately perpendicular to the thickness direction (T axis direction). For example, the length direction (L axis direction) can be a direction in which the first external electrode 131 and the second external electrode 132 are opposite to each other. The width direction (W axis direction) can be a direction extending parallel to the wide surface (main surface) of the sheet component, and can be approximately perpendicular to the thickness direction (T axis direction) and the length direction (L axis direction). The length of the sheet component in the length direction (L axis direction) can be greater than the width in the width direction (W axis direction).
[0050] Reference Figures 1 to 4 , the multilayer ceramic capacitor 100 according to the embodiment includes a capacitor body 110 and external electrodes 131 and 132, which are disposed outside the capacitor body 110. The external electrodes 131 and 132 may include a first external electrode 131 and a second external electrode 132, which are disposed at opposite ends of the capacitor body 110 in the length direction (L-axis direction).
[0051] For example, the capacitor body 110 may have a substantially hexahedral shape.
[0052] For the convenience of describing the embodiments, the two surfaces of the capacitor body 110 opposite to each other in the thickness direction (T-axis direction) are referred to as the first surface and the second surface, the two surfaces connected to the first surface and the second surface and opposite to each other in the length direction (L-axis direction) are referred to as the third surface and the fourth surface, and the two surfaces connected to the first surface and the second surface and connected to the third surface and the fourth surface and opposite to each other in the width direction (W-axis direction) are referred to as the fifth surface and the sixth surface.
[0053] As an example, the first surface as the lower surface may be a mounting surface. In addition, the first to sixth surfaces may be flat, but the embodiment is not limited thereto. For example, the first to sixth surfaces may be curved surfaces having a convex central portion, and the edges as the boundaries of the respective surfaces may be rounded.
[0054] The shape and size of the capacitor body 110 and the number of stacked dielectric layers 111 are not limited to those shown in the drawings of the embodiment.
[0055] The capacitor body 110 includes a plurality of dielectric layers 111 and a plurality of internal electrode layers 121 and 122. Specifically, the capacitor body 110 includes a plurality of dielectric layers 111 and first and second internal electrodes 121 and 122 alternately arranged in a thickness direction (T-axis direction) with the dielectric layers 111 interposed therebetween.
[0056] A detailed description about the capacitor body 110 will be provided later.
[0057] External electrode
[0058] Reference Figure 2 and Figure 4 The external electrodes 131 and 132 (ie, the first external electrode 131 and the second external electrode 132 ) are provided with voltages of different polarities and may be electrically connected to the exposed portions of the first internal electrode 121 and the exposed portions of the second internal electrode 122 , respectively.
[0059] According to the above configuration, when a predetermined voltage is applied to the first external electrode 131 and the second external electrode 132, charges are accumulated between the first internal electrode 121 and the second internal electrode 122 facing each other. At this time, the capacitance of the multilayer ceramic capacitor 100 is proportional to the overlapping area of the first internal electrode 121 and the second internal electrode 122 overlapping each other in the T-axis direction in the active region.
[0060] The first outer electrode 131 may include a first connecting portion arranged on the third surface of the capacitor body 110 and connected to the first inner electrode 121, and a first band portion arranged on the edge where the third surface of the capacitor body 110 intersects with the first surface and the second surface and / or the fifth surface and the sixth surface, and the second outer electrode 132 may include a second connecting portion arranged on the fourth surface of the capacitor body 110 and connected to the second inner electrode 122, and a second band portion arranged on the edge where the fourth surface of the capacitor body 110 intersects with the first surface and the second surface and / or the fifth surface and the sixth surface.
[0061] The first and second band portions may extend from the first and second connecting portions, respectively, to a portion of the first and second surfaces and / or a portion of the fifth and sixth surfaces of the capacitor body 110. The first and second band portions may be used to improve the bonding strength of the first and second external electrodes 131 and 132 to the capacitor body 110.
[0062] The external electrodes 131 and 132 include lower layers 10 and 30 and upper layers 20 and 40, the lower layers 10 and 30 are located on the surface of the capacitor body 110 to be electrically connected to at least one of the internal electrode layers 121 and 122, and the upper layers 20 and 40 are configured to cover the lower layers 10 and 30 (for example, located on the lower layers 10 and 30). Specifically, the first external electrode 131 includes a first lower layer 10 and a first upper layer 20, the first lower layer 10 is located on the surface of the capacitor body 110 to be electrically connected to the first internal electrode 121, and the first upper layer 20 is configured to cover the first lower layer 10 (for example, located on the first lower layer 10). In addition, the second external electrode 132 includes a second lower layer 30 and a second upper layer 40, the second lower layer 30 is located on the surface of the capacitor body 110 to be electrically connected to the second internal electrode 122, and the second upper layer 40 is configured to cover the second lower layer 30 (for example, located on the second lower layer 30).
[0063] The lower layers 10 and 30 and the upper layers 20 and 40 may include glass having different compositions. When the external electrode is formed into at least two layers and each layer includes a glass component of a different composition, an external electrode having not only excellent contact with the internal electrode layer but also excellent corrosion resistance and moisture resistance reliability by preventing penetration of moisture and plating solution can be ensured. Therefore, a multilayer ceramic capacitor having improved reliability can be realized.
[0064] The lower layers 10 and 30 may include a first glass, and the first glass may include aluminum (Al). In addition, the upper layers 20 and 40 may include a second glass, and the second glass may include aluminum (Al).
[0065] In more detail, the amount of aluminum (Al) included in the lower layers 10 and 30 may be greater than 0 atomic % and less than or equal to 8 atomic %, for example, 0.1 atomic % to 7.9 atomic %, and for example, 0.5 atomic % to 7.7 atomic %. In addition, the amount of aluminum (Al) included in the upper layers 20 and 40 may be greater than or equal to 10 atomic % and less than or equal to 20 atomic %, for example, 11 atomic % to 19 atomic %, and for example, 12 atomic % to 18 atomic %. When each of the lower layers 10 and 30 and the upper layers 20 and 40 includes aluminum (Al) within the above content range as a glass component, an external electrode can be ensured that not only the contact with the internal electrode layer is excellent, but also the corrosion resistance and moisture resistance reliability are excellent by preventing the penetration of moisture and plating solution. A multilayer ceramic capacitor including such an external electrode may have improved reliability.
[0066] As an example, an atomic ratio of the amount of aluminum (Al) included in the second glass of the upper layers 20 and 40 to the amount of aluminum (Al) included in the first glass of the lower layers 10 and 30 may be greater than 2 and less than or equal to 100, for example, the atomic ratio may be 3 to 80. When the atomic ratio of aluminum (Al) included in the lower layers 10 and 30 and the upper layers 20 and 40 is within the above range, an outer electrode having excellent contact with an inner electrode layer and excellent corrosion resistance and moisture resistance reliability may be ensured, and thus, the reliability of the multilayer ceramic capacitor may be improved.
[0067] The aluminum (Al) included in the first glass may be a component derived from aluminum oxide added to a paste for forming a lower layer when forming an external electrode, and the aluminum (Al) included in the second glass may be a component derived from aluminum oxide added to a paste for forming an upper layer when forming an external electrode.
[0068] In addition to aluminum (Al), the first glass of the lower layers 10 and 30 may also include lithium (Li), sodium (Na), iron (Fe), barium (Ba), calcium (Ca), zinc (Zn), boron (B), silicon (Si), tin (Sn), or combinations thereof.
[0069] Lithium (Li), sodium (Na), and iron (Fe) that may be included in the first glass may be components derived from lithium oxide (Li2O), sodium oxide (Na2O), and iron oxide (Fe2O3), respectively, added to the paste for forming the upper layer when forming the external electrode. That is, the additives (lithium (Li), sodium (Na), and iron (Fe) that may be included in the first glass) may be components that are partially diffused into the lower layer when forming the upper layer. In addition, barium (Ba), calcium (Ca), zinc (Zn), boron (B), and silicon (Si) that may be included in the first glass may be components derived from barium oxide (BaO), calcium oxide (CaO), zinc oxide (ZnO), boron oxide (B2O3), and silicon dioxide (SiO2), respectively, added to the paste for forming the lower layer when forming the external electrode.
[0070] As an example, the first glass may include aluminum (Al), barium (Ba), and zinc (Zn). In addition, the first glass may be a Ba / Zn-based glass in which the sum of the components of barium (Ba) and zinc (Zn) accounts for the largest portion of the total components of the first glass. For example, the sum of the components of barium (Ba) and zinc (Zn) may be 50 atomic % to 95 atomic % with respect to the total amount of the components of the first glass, and may be 55 atomic % to 90 atomic %. When the first glass has a composition within the above range, an external electrode having excellent connectivity (i.e., contact) with an internal electrode layer may be obtained.
[0071] In addition to aluminum (Al), the second glass of the upper layers 20 and 40 may also include lithium (Li), sodium (Na), iron (Fe), barium (Ba), calcium (Ca), zinc (Zn), boron (B), silicon (Si), tin (Sn), or a combination thereof.
[0072] Lithium (Li), sodium (Na), and iron (Fe) that may be included in the second glass may be components derived from lithium oxide (Li2O), sodium oxide (Na2O), and iron oxide (Fe2O3), respectively, added to a paste for forming an upper layer when forming an external electrode. In addition, barium (Ba), calcium (Ca), zinc (Zn), boron (B), and silicon (Si) that may be included in the second glass may be components derived from barium oxide (BaO), calcium oxide (CaO), zinc oxide (ZnO), boron oxide (B2O3), and silicon dioxide (SiO2), respectively, added to a paste for forming an upper layer when forming an external electrode. That is, the second glass may include lithium (Li), the first glass may include lithium (Li), and the atomic ratio of the amount of lithium (Li) included in the second glass to the amount of lithium (Li) included in the first glass may be greater than 1.
[0073] As an example, the second glass may include aluminum (Al) and silicon (Si). In addition, the second glass may be an Al / Si-based glass in which the sum of the components of aluminum (Al) and silicon (Si) accounts for a major portion of the total components of the second glass. For example, the sum of the components of aluminum (Al) and silicon (Si) may be 20 atomic % to 50 atomic % and may be 22 atomic % to 40 atomic % relative to the total amount of the components of the second glass. When the second glass has a composition within the above range, an external electrode having excellent corrosion resistance and moisture resistance reliability may be obtained.
[0074] When forming the external electrode, in the case of using Ba / Zn-based glass alone, although the contact with the internal electrode layer is excellent, the reliability may not be ensured because the Ba / Zn-based glass may be corroded by the plating solution, and in the case of using Al / Si-based glass alone, although the reliability is excellent due to the strong corrosion resistance to the plating solution, the contact failure with the internal electrode layer may occur due to poor contact with the metal. According to the embodiment, by forming the external electrode into at least two layers including a lower layer corresponding to the Ba / Zn-based glass and an upper layer corresponding to the Al / Si-based glass, an external electrode having not only excellent contact with the internal electrode layer but also excellent corrosion resistance to the plating solution and moisture resistance reliability can be ensured. Therefore, a multilayer ceramic capacitor with excellent reliability can be realized.
[0075] In addition, for example, the first glass of the lower layers 10 and 30 and the second glass of the upper layers 20 and 40 may include sodium (Na). In this case, the atomic ratio of the amount of sodium (Na) included in the second glass to the amount of sodium (Na) included in the first glass may be greater than 2 and less than or equal to 100, for example, the atomic ratio may be 3 to 80. When the atomic ratio of sodium (Na) included in the lower layers 10 and 30 and the upper layers 20 and 40 is within the above range, an external electrode having excellent contact with the internal electrode layer and excellent corrosion resistance and moisture resistance reliability may be ensured.
[0076] As an example, the first glass of the lower layers 10 and 30 and the second glass of the upper layers 20 and 40 may include iron (Fe). In this case, the atomic ratio of the amount of iron (Fe) included in the second glass to the amount of iron (Fe) included in the first glass may be greater than 2 and less than or equal to 100, for example, the atomic ratio may be 3 to 80. When the atomic ratio of iron (Fe) included in the lower layers 10 and 30 and the upper layers 20 and 40 is within the above range, an external electrode having excellent contact with the internal electrode layer and excellent corrosion resistance and moisture resistance reliability may be ensured.
[0077] It may be confirmed through scanning electron microscope (SEM) analysis that the external electrodes 131 and 132 according to the embodiment are formed to include lower layers 10 and 30 and upper layers 20 and 40 .
[0078] SEM analysis can be performed as follows. The multilayer ceramic capacitor 100 can be placed in an epoxy resin mixture liquid and cured, and then polished using sandpaper and diamond suspension so that a cross-sectional sample having an LT surface (cross-section in the length direction and thickness direction) can be obtained to be able to observe the external electrode. Subsequently, the obtained cross-sectional sample can be measured by a scanning electron microscope (SEM). For example, the SEM measurement can be performed using Tescan's Vega3 under the conditions of 20kV, 0.2nA and 3k times magnification.
[0079] In addition, the composition of the components included in the above-mentioned lower layers 10 and 30 and the upper layers 20 and 40 (more specifically, the atomic % and atomic ratio of aluminum (Al), silicon (Si), barium (Ba), zinc (Zn), sodium (Na), iron (Fe), etc. in each layer) may be confirmed by scanning electron microscope-energy dispersive spectrometer (SEM-EDS) analysis or electron probe microanalyzer (EPMA). Even if not described in the present disclosure, other methods and / or tools understood by those of ordinary skill in the art may be used.
[0080] SEM-EDS analysis can be performed as follows. First, a cross-sectional sample can be obtained from the multilayer ceramic capacitor 100 by the above method. Subsequently, the obtained cross-sectional sample can be measured by a scanning electron microscope (SEM). The SEM measurement can be performed, for example, by using Tescan's Vega3 under the conditions of 20kV, 0.2nA and 6005 times magnification. Subsequently, the SEM image of the measured cross-sectional sample can be subjected to energy dispersive spectrometer (EDS) analysis to confirm the content of each component present in the lower layer and the upper layer of the outer electrode.
[0081] In addition, EPMA analysis can be performed as follows. First, a cross-sectional sample can be obtained from the multilayer ceramic capacitor 100 by the above method. The obtained cross-sectional sample can be subjected to electron probe microanalyzer (EPMA) analysis under the conditions of a voltage of 15 kV and a magnification of 10 k, and the mapping and content of each element present in the lower and upper layers of the external electrode can be confirmed.
[0082] The lower layers 10 and 30 and the upper layers 20 and 40 may be sintered metal layers of external electrodes.
[0083] At least one of the lower layers 10 and 30 and the upper layers 20 and 40 may further include a conductive metal. That is, one of the lower layers 10 and 30 and the upper layers 20 and 40 may include a conductive metal, and / or all of the lower layers 10 and 30 and the upper layers 20 and 40 may include a conductive metal.
[0084] The conductive metal may include copper (Cu), nickel (Ni), silver (Ag), palladium (Pd), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), lead (Pb), their alloys, or combinations thereof, for example, may include copper (Cu) or a copper (Cu) alloy.
[0085] When the conductive metal includes copper (Cu), the metal other than copper (Cu) may be included in an amount of 5 mol parts or less relative to 100 mol parts of copper (Cu).
[0086] The amount of the conductive metal included in the lower layers 10 and 30 may be 80 wt % to 99 wt % relative to the total amount of the lower layers, and the amount of the conductive metal included in the upper layers 20 and 40 may be 80 wt % to 99 wt % relative to the total amount of the upper layers.
[0087] like Figure 2As shown, the external electrodes 131 and 132 may include a central portion A and a corner portion B, the central portion A including the central point of the multilayer ceramic capacitor 100 in the thickness direction (T-axis direction), and the corner portion B including the corner point of the multilayer ceramic capacitor 100. That is, in the external electrodes 131 and 132, the central portion A may be a portion disposed at the central point of the third surface and the fourth surface in the thickness direction (T-axis direction), and the corner portion B may be a portion disposed at a point where the three surfaces of the capacitor body 110 intersect.
[0088] Since the corner portion B of the external electrodes 131 and 132 according to the embodiment includes the lower layers 10 and 30 and the upper layers 20 and 40, that is, forms at least a double layer, the thickness of the corner portion B can be increased. The corner portion B may be one of the permeation paths of the plating solution. According to the embodiment, by increasing the thickness of the corner portion B, the permeation of the plating solution can be prevented, and thus, the corrosion resistance and moisture resistance reliability can be improved.
[0089] As an example, the thickness ratio of the corner portion B to the center portion A of the external electrodes 131 and 132 may be 0.1 to 0.5, for example, 0.15 to 0.45. When the thickness ratio of the corner portion B to the center portion A of the external electrodes 131 and 132 is within the above range, corrosion resistance and moisture resistance reliability may be improved.
[0090] The thickness of the center portion A and the corner portion B of the outer electrodes 131 and 132 may be measured by scanning electron microscope (SEM) analysis. The SEM analysis may be performed in the same manner as the SEM analysis method for confirming the components of the lower layers 10 and 30 and the upper layers 20 and 40 as described above. Even if not described in the present disclosure, other methods and / or tools understood by those of ordinary skill in the art may be used.
[0091] The external electrodes 131 and 132 may further include a conductive resin layer disposed on the upper layers 20 and 40 to cover the above-described lower layers 10 and 30 and the upper layers 20 and 40 , and a plating layer disposed to cover the conductive resin layer.
[0092] The conductive resin layer extends to the first and second surfaces and / or the fifth and sixth surfaces of the capacitor body 110, and the length of the region (i.e., the band portion) where the conductive resin layer extends and is provided to the first and second surfaces and / or the fifth and sixth surfaces of the capacitor body 110 may be longer than the length of the region (i.e., the band portion) where the upper layers 20 and 40 extend and are provided to the first and second surfaces and / or the fifth and sixth surfaces of the capacitor body 110. That is, the conductive resin layer may be formed on the upper layers 20 and 40, and may be formed in a form that completely covers the upper layers 20 and 40.
[0093] The conductive resin layer may include resin and conductive metal.
[0094] The resin included in the conductive resin layer may be implemented by a material having adhesiveness and shock absorption and capable of forming a paste when mixed with the conductive metal powder, but is not limited thereto. For example, the resin may include phenolic resin, acrylic resin, silicone resin, epoxy resin, or polyimide resin.
[0095] The conductive metal included in the conductive resin layer serves to electrically connect with the internal electrode layers 121 and 122 and / or to electrically connect with the lower layers 10 and 30 and the upper layers 20 and 40 .
[0096] The conductive metal included in the conductive resin layer may have a spherical shape, a flake shape, or a combination thereof. That is, the conductive metal may be formed only in a flake form, only in a spherical form, or in a mixed form of a flake form and a spherical form.
[0097] Here, the spherical shape may also include a shape that is not a perfect sphere, for example, a shape in which the length ratio of the major axis to the minor axis (major axis / minor axis) is 1.45 or less. The flake shape refers to a flat and elongated shape, and is not particularly limited. For example, the length ratio of the major axis to the minor axis (major axis / minor axis) of the flake shape may be 1.95 or more.
[0098] The plating layer may include a single nickel (Ni), copper (Cu), tin (Sn), palladium (Pd), platinum (Pt), gold (Au), silver (Ag), tungsten (W), titanium (Ti) or lead (Pb) or an alloy thereof. For example, the plating layer may be a nickel (Ni) plating layer or a tin (Sn) plating layer, may be a nickel (Ni) plating layer and a tin (Sn) plating layer stacked in sequence, or may be a tin (Sn) plating layer, a nickel (Ni) plating layer and a tin (Sn) plating layer stacked in sequence. In addition, the plating layer may include a plurality of nickel (Ni) plating layers and / or a plurality of tin (Sn) plating layers.
[0099] The plating layer may improve the mountability with a substrate, structural reliability, durability to the outside, heat resistance, and equivalent series resistance (ESR) of the multilayer ceramic capacitor 100 .
[0100] Capacitor body
[0101] The capacitor body 110 includes a plurality of dielectric layers 111 and a plurality of internal electrode layers 121 and 122. Specifically, the capacitor body 110 includes a plurality of dielectric layers 111 and first and second internal electrodes 121 and 122 alternately arranged in a thickness direction (T-axis direction) with the dielectric layers 111 interposed therebetween.
[0102] At this time, the adjacent dielectric layers 111 of the capacitor body 110 may be integrated to such an extent that it is difficult to distinguish the boundaries between the adjacent dielectric layers 111 without using a scanning electron microscope (SEM).
[0103] The capacitor body 110 may include an active region, which is a portion contributing to forming the capacitance of the multilayer ceramic capacitor 100. Specifically, the active region may be a region where the first and second internal electrodes 121 and 122 stacked in the thickness direction (T-axis direction) overlap.
[0104] In addition, the capacitor body 110 may further include a cover region and a side edge region.
[0105] The cover region is a thickness direction edge portion and may be located on the upper and lower surfaces of the active region in the thickness direction (T-axis direction). The cover region may be a single dielectric layer or two or more dielectric layers stacked on the upper and lower surfaces of the active region, respectively.
[0106] The side edge region is a width direction edge portion and may be located on both side surfaces of the effective region in the width direction (W axis direction). The side edge region may be formed as follows: when a conductive paste for an inner electrode layer is applied on the surface of a dielectric green sheet, the conductive paste is applied only on a partial area of the surface of the dielectric green sheet, and the conductive paste is not applied on an area of the surface of the dielectric green sheet where the side edge region is to be formed, and then stacking and firing are performed.
[0107] The cover region and the side edge region serve to prevent damage to the first and second internal electrodes 121 and 122 due to physical stress or chemical stress.
[0108] The dielectric layer 111 may include a barium titanate-based main component.
[0109] The barium titanate-based main component is a dielectric base material, has a high dielectric constant, and contributes to forming the dielectric constant of the multilayer ceramic capacitor 100 .
[0110] For example, the barium titanate-based main component may include BaTiO3, Ba(Ti,Zr)O3, Ba(Ti,Sn)O3, (Ba,Ca)TiO3, (Ba,Ca)(Ti,Zr)O3, (Ba,Ca)(Ti,Sn)O3, (Ba,Sr)TiO3, (Ba,Sr)(Ti,Zr)O3, (Ba,Sr)(Ti,Sn)O3, or a combination thereof.
[0111] The dielectric layer 111 may further include a secondary component. For example, the secondary component may include manganese (Mn), chromium (Cr), silicon (Si), aluminum (Al), magnesium (Mg), tin (Sn), antimony (Sb), germanium (Ge), gallium (Ga), indium (In), barium (Ba), lanthanum (La), yttrium (Y), actinium (Ac), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), hafnium (Hf), vanadium (V), or a combination thereof.
[0112] The average thickness (average length in the T-axis direction) of the dielectric layer 111 can be 2.0 μm to 8.0 μm, for example, 2.4 μm to 7.8 μm. When the average thickness of the dielectric layer 111 is within the above range, the reliability of the multilayer ceramic capacitor is excellent. As described above, in the scanning electron microscope (SEM) image of the measured cross-sectional sample, the center point of the dielectric layer 111 in the length direction (L-axis direction) or the width direction (W-axis direction) is used as a reference point, and the arithmetic mean of the thickness of the dielectric layer 111 can be obtained by measuring the thickness of the dielectric layer 111 at 10 points spaced apart from the reference point by a predetermined interval. The interval between the 10 points can be adjusted according to the scale of the SEM image, for example, it can be 1 μm to 100 μm, 1 μm to 50 μm, or 1 μm to 10 μm. At this time, the 10 points must all be located within the dielectric layer 111, and if the 10 points are not all located within the dielectric layer 111, the positions of the reference points may be changed, or the intervals between the 10 points may be adjusted.
[0113] The internal electrode layers 121 and 122 (i.e., the first internal electrode 121 and the second internal electrode 122) are electrodes having different polarities, are alternately arranged relative to each other along the T-axis direction with the dielectric layer 111 interposed therebetween, and may have first ends exposed through the third and fourth surfaces of the capacitor body 110, respectively.
[0114] The first and second internal electrodes 121 and 122 may be electrically insulated from each other by a dielectric layer 111 disposed in between.
[0115] Ends of the first and second internal electrodes 121 and 122 alternately exposed through the third and fourth surfaces of the capacitor body 110 may be electrically connected to the first and second external electrodes 131 and 132 , respectively.
[0116] The first and second internal electrodes 121 and 122 may include a conductive metal, for example, a metal such as Ni, Cu, Ag, Pd, Au, or an alloy thereof such as an Ag—Pd alloy.
[0117] In addition, the first and second internal electrodes 121 and 122 may include dielectric particles having the same composition as the ceramic material included in the dielectric layer 111 .
[0118] The first and second internal electrodes 121 and 122 may be formed using a conductive paste including a conductive metal. A printing method of the conductive paste may be a screen printing method or a gravure printing method.
[0119] The average thickness of the first internal electrode 121 and the second internal electrode 122 may be 0.1 μm to 2 μm. The average thickness of the first internal electrode 121 and the second internal electrode 122 may be measured by SEM analysis. Here, since the method for measuring the average thickness of the internal electrode is the same as the method for measuring the average thickness of the dielectric layer 111 described above, a description thereof will be omitted.
[0120] The capacitor body 110 may be formed by firing a stack structure in which a plurality of dielectric layers 111 and a plurality of internal electrode layers 121 and 122 are stacked.
[0121] Hereinafter, a method of manufacturing the multilayer ceramic capacitor 100 according to an embodiment will be described.
[0122] Method for manufacturing multilayer ceramic capacitor
[0123] According to an embodiment, a manufacturing method of a multilayer ceramic capacitor 100 may include: applying a first paste for forming a lower layer of external electrodes 131 and 132 on a surface of a capacitor body 110 including a dielectric layer 111 and internal electrode layers 121 and 122, the lower layer including a first glass; forming lower layers 10 and 30 by sintering the first paste; applying a second paste for forming an upper layer of the external electrodes 131 and 132 on the lower layers 10 and 30 of the external electrodes 131 and 132, the upper layer including a second glass; and forming upper layers 20 and 40 by sintering the second paste.
[0124] In addition, according to another embodiment, a manufacturing method of a multilayer ceramic capacitor 100 may include: applying a first paste for forming a lower layer of external electrodes 131 and 132 on a surface of a capacitor body 110 including a dielectric layer 111 and internal electrode layers 121 and 122, the lower layer including a first glass; applying a second paste for forming an upper layer of the external electrodes 131 and 132 on the first paste, the upper layer including a second glass; and forming the external electrodes 131 and 132 including lower layers 10 and 30 and upper layers 20 and 40 by sintering the capacitor body coated with the first paste and the second paste.
[0125] First, a method of preparing the capacitor body 110 will be described.
[0126] The capacitor body 110 may be manufactured by manufacturing a dielectric green sheet by using a dielectric slurry and forming a conductive paste layer on a surface of the dielectric green sheet; manufacturing a dielectric green sheet stack by stacking the dielectric green sheets formed with the conductive paste layer; and firing the dielectric green sheet stack.
[0127] The dielectric slurry may be prepared by mixing a barium titanate-based main component powder and an optional sub-component powder.
[0128] Since the barium titanate-based main component powder is the same as the barium titanate-based main component contained in the dielectric layer, a description thereof is omitted here.
[0129] For example, the auxiliary component powder may include manganese (Mn), chromium (Cr), silicon (Si), aluminum (Al), magnesium (Mg), tin (Sn), antimony (Sb), germanium (Ge), gallium (Ga), indium (In), barium (Ba), lanthanum (La), yttrium (Y), actinium (Ac), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), hafnium (Hf), vanadium (V) or a combination thereof, but is not limited thereto. The amount of each auxiliary component powder may be 0.01 to 5 parts by mole relative to 100 parts by mole of the barium titanate-based main component powder.
[0130] The subcomponent powder may be used in the form of an oxide or salt compound containing each metal, or may be used in the form of a sol dispersed in an organic solvent.
[0131] In addition, the dielectric slurry may be prepared by further mixing additives such as a dispersant, a binder, a plasticizer, a lubricant, and an antistatic agent and a solvent.
[0132] The barium titanate-based main component powder and the optional auxiliary component powder can be mixed by using a wet ball mill or a stirred mill. When zirconia balls are used in a wet ball mill, a plurality of zirconia balls having a diameter of 0.1 mm to 10 mm can be used for wet mixing for 8 to 48 hours, for example, 10 hours or 24 hours.
[0133] After firing, the prepared dielectric slurry is formed into a dielectric layer.
[0134] As a method of forming the prepared dielectric slurry into a sheet, a tape molding method such as a doctor blade method, a calendar roll method, etc., for example, a roll forming coater using a manifold discharge method can be used, and then a dielectric green sheet can be obtained by drying the formed body.
[0135] In order to form a conductive paste layer that becomes an internal electrode layer after firing, the conductive paste can be prepared by mixing a conductive powder made of a conductive metal or an alloy thereof, a binder, and a solvent. In addition, if necessary, barium titanate powder can be mixed together as a co-material. The co-material can be used to suppress the sintering of the conductive powder during the firing process. The conductive paste layer is formed by applying the conductive paste to the surface of the dielectric green sheet in a predetermined pattern using various printing methods such as screen printing or transfer printing.
[0136] The conductive powder may include nickel (Ni) or a nickel (Ni) alloy.
[0137] Next, a dielectric green sheet stack structure is prepared by stacking a plurality of dielectric green sheets having internal electrode patterns formed thereon and then pressing the plurality of dielectric green sheets in a stacking direction. In addition, in the process of preparing the dielectric green sheet stack structure, dielectric green sheets having no internal electrode patterns formed thereon may be stacked so that the dielectric green sheets having no internal electrode patterns formed thereon are located on the upper and lower surfaces of the stack structure formed by stacking a plurality of dielectric green sheets having internal electrode patterns formed thereon in the stacking direction.
[0138] Alternatively, a step of cutting the prepared dielectric green sheet stack structure into a predetermined size by dicing or the like may be performed.
[0139] In addition, if necessary, the dielectric green sheet stack structure may be cured and dried to remove the plasticizer, etc., and after curing and drying, the dielectric green sheet stack structure may be drum polished using a horizontal centrifugal drum machine, etc. In drum polishing, the dielectric green sheet stack structure is placed in a drum container having a medium and a polishing liquid, and a rotational motion or vibration is applied to the drum container, so that unnecessary portions (such as burrs generated during cutting) can be polished. In addition, after drum polishing, the dielectric green sheet stack structure may be washed with a cleaning solution (such as water) and dried.
[0140] Subsequently, after the binder removal process and firing of the dielectric green sheet stack structure, a capacitor body can be prepared.
[0141] The conditions for removing the binder may be appropriately adjusted according to the components of the dielectric layer or the inner electrode layer. For example, the temperature increase rate during the binder removal process may be 5° C. / hour to 300° C. / hour, the carrier temperature may be 180° C. to 400° C., and the temperature holding time may be 0.5 hour to 24 hours. The process atmosphere for binder removal may be air or a reducing atmosphere.
[0142] The conditions of the firing treatment may be appropriately adjusted according to the main component composition of the dielectric layer or the main component composition of the inner electrode layer. For example, the firing may be performed at a temperature of 1100° C. to 1400° C., and may be performed at a temperature of 1200° C. to 1350° C. In addition, the firing may be performed for 0.5 hours to 8 hours, for example, 1 hour to 3 hours. In addition, the firing may be performed in a reducing atmosphere, for example, in a humidified mixed gas of nitrogen and hydrogen. When the inner electrode layer includes nickel (Ni) or a nickel (Ni) alloy, the oxygen partial pressure in the firing atmosphere may be 1.0×10 -14 MPa to 1.0×10 -10 MPa.
[0143] After firing, annealing may be performed as needed. Annealing is a process for reoxidizing the dielectric layer, and if firing is performed in a reducing atmosphere, annealing may be performed. The conditions of the annealing process may also be appropriately adjusted according to the composition of the dielectric layer. For example, the annealing temperature may be 950°C to 1150°C, the time may be 0 to 20 hours, and the temperature increase rate may be 50°C / hour to 500°C / hour. The annealing atmosphere may be a humidified nitrogen (N2) atmosphere, and the oxygen partial pressure may be 1.0×10 - 9 MPa to 1.0×10 -5 MPa.
[0144] In the binder removal process, the firing process, or the annealing process, for example, a wetting agent may be used to wet the nitrogen gas or the mixed gas. In this case, the water temperature may be 5° C. to 75° C. The binder removal process, the firing process, and the annealing process may be performed sequentially or independently.
[0145] Optionally, the third surface and the fourth surface of the prepared capacitor body 110 may be subjected to surface treatment (such as sandblasting, laser irradiation, barrel polishing, etc.). By performing this surface treatment, the end of the first inner electrode and the end of the second inner electrode may be exposed to the third surface and the fourth surface, respectively, so that the electrical connection between the first outer electrode and the first inner electrode and between the second outer electrode and the second inner electrode may be improved, and the alloy portion may be easily formed.
[0146] Hereinafter, a method of preparing the external electrodes 131 and 132 will be described.
[0147] The lower layers 10 and 30 are formed by coating a first paste for forming a lower layer on the surface of the manufactured capacitor body 110 and sintering, and then, a second paste for forming an upper layer is coated on the lower layers 10 and 30 and sintered to form the upper layers 20 and 40, so that the external electrodes 131 and 132 can be prepared. In addition, the first paste for forming a lower layer is coated on the surface of the manufactured capacitor body 110, and the second paste for forming an upper layer is coated on the first paste and sintered, thereby forming the lower layers 10 and 30 and the upper layers 20 and 40, so that the external electrodes 131 and 132 can be prepared.
[0148] The first paste for forming the lower layer may include a first glass composition for forming a first glass, and the first glass composition may include aluminum oxide (Al2O3). In addition, the second paste for forming the upper layer may include a second glass composition for forming a second glass, and the second glass composition may include aluminum oxide (Al2O3).
[0149] In more detail, the amount of aluminum oxide (Al2O3) included in the first paste for forming the lower layer may be greater than 0 mol parts and less than or equal to 8 mol parts, for example, 0.1 mol parts to 7.9 mol parts, and for example, 0.5 mol parts to 7.7 mol parts, relative to the total amount of 100 mol parts of the first glass composition. In addition, the amount of aluminum oxide (Al2O3) included in the second paste for forming the upper layer may be greater than or equal to 10 mol parts and less than or equal to 20 mol parts, for example, 11 mol parts to 19 mol parts, and for example, 12 mol parts to 18 mol parts, relative to the total amount of 100 mol parts of the second glass composition. When each of the first paste for forming the lower layer and the second paste for forming the upper layer includes aluminum oxide (Al2O3) within the above content range as a glass component, the following external electrode can be prepared: not only the contact with the internal electrode layer is excellent, but also the corrosion resistance and moisture resistance reliability are excellent by preventing the penetration of moisture and plating solution.
[0150] The first glass composition of the first paste for forming the lower layer may further include barium oxide (BaO), calcium oxide (CaO), zinc oxide (ZnO), boron oxide (B2O3), silicon dioxide (SiO2), or a combination thereof.
[0151] The amount of barium oxide (BaO) may be 10 to 40 molar parts, for example, 15 to 35 molar parts, relative to 100 molar parts of the total amount of the first glass composition. The amount of calcium oxide (CaO) may be 1 to 20 molar parts, for example, 5 to 15 molar parts, relative to 100 molar parts of the total amount of the first glass composition. The amount of zinc oxide (ZnO) may be 10 to 40 molar parts, for example, 15 to 35 molar parts, relative to 100 molar parts of the total amount of the first glass composition. The amount of boron oxide (B2O3) may be 10 to 40 molar parts, for example, 15 to 35 molar parts, relative to 100 molar parts of the total amount of the first glass composition. The amount of silicon dioxide (SiO2) may be 1 to 20 molar parts, for example, 5 to 15 molar parts, relative to 100 molar parts of the total amount of the first glass composition. When the components of the first glass composition of the first paste for forming the lower layer are within the above content range, an external electrode excellent in contact with the internal electrode layer and in corrosion resistance and moisture resistance reliability may be prepared.
[0152] The second glass composition of the second paste used to form the upper layer may also include lithium oxide (Li2O), sodium oxide (Na2O), barium oxide (BaO), calcium oxide (CaO), zinc oxide (ZnO), boron oxide (B2O3), silicon dioxide (SiO2), iron oxide (Fe2O3) or a combination thereof.
[0153] The amount of lithium oxide (Li2O) may be 1 to 20 molar parts, for example, 5 to 15 molar parts, relative to 100 molar parts of the total amount of the second glass composition. The amount of sodium oxide (Na2O) may be 1 to 20 molar parts, for example, 3 to 15 molar parts, relative to 100 molar parts of the total amount of the second glass composition. The amount of barium oxide (BaO) may be 10 to 40 molar parts, for example, 15 to 35 molar parts, relative to 100 molar parts of the total amount of the second glass composition. The amount of calcium oxide (CaO) may be 1 to 20 molar parts, for example, 5 to 15 molar parts, relative to 100 molar parts of the total amount of the second glass composition. The amount of zinc oxide (ZnO) may be 1 to 20 molar parts, for example, 5 to 15 molar parts, relative to 100 molar parts of the total amount of the second glass composition. Relative to 100 mol parts of the total amount of the second glass composition, the amount of boron oxide (B2O3) can be 10 mol parts to 40 mol parts, for example, 15 mol parts to 35 mol parts. Relative to 100 mol parts of the total amount of the second glass composition, the amount of silicon dioxide (SiO2) can be 1 mol parts to 20 mol parts, for example, 5 mol parts to 15 mol parts. Relative to 100 mol parts of the total amount of the second glass composition, the amount of iron oxide (Fe2O3) can be 0.1 mol parts to 10 mol parts, for example, 0.5 mol parts to 5 mol parts. When the components of the second glass composition used to form the second paste of the upper layer are within the above-mentioned content range, an external electrode that is excellent in contact with the internal electrode layer and in corrosion resistance and moisture resistance reliability can be prepared.
[0154] At least one of the first paste for forming the lower layer and the second paste for forming the upper layer may further include a conductive metal. That is, one of the first paste for forming the lower layer and the second paste for forming the upper layer may include a conductive metal, and / or both of the first paste for forming the lower layer and the second paste for forming the upper layer may include a conductive metal.
[0155] The conductive metal may include copper (Cu), nickel (Ni), silver (Ag), palladium (Pd), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), lead (Pb), their alloys, or combinations thereof, for example, may include copper (Cu) or a copper (Cu) alloy.
[0156] As an example, the amount of conductive metal included in the paste for forming the lower layer may be 80wt% to 99wt% relative to the total amount of paste for forming the lower layer, and the amount of conductive metal included in the paste for forming the upper layer may be 80wt% to 99wt% relative to the total amount of paste for forming the upper layer.
[0157] At least one of the first paste for forming the lower layer and the second paste for forming the upper layer may further include a binder, a solvent, a dispersant, a plasticizer, an oxide powder, or the like.
[0158] The binder may be, for example, ethyl cellulose, acrylic acid, butyral, etc., and the solvent may be, for example, an organic solvent or an aqueous solvent, for example, terpineol, butyl carbitol, ethanol, methyl ethyl ketone, acetone, toluene, etc.
[0159] The method of coating the first paste for forming the lower layer on the outer surface of the capacitor body 110 may include a dipping method, various printing methods (such as a screen printing method), a coating method using a dispenser, etc., and a spraying method using a sprayer. The first paste for forming the lower layer may be applied to at least the third and fourth surfaces of the capacitor body 110, and optionally to portions of the first, second, fifth, and / or sixth surfaces on which the band portions of the first and second external electrodes are formed.
[0160] The sintering may be performed at a temperature of 700° C. to 1000° C. for 0.1 hour to 3 hours.
[0161] Alternatively, the conductive resin layer may be formed by coating and curing a paste for forming the conductive resin layer on a region of the outer surface of the capacitor body 110 where the upper layers 20 and 40 are formed on the lower layers 10 and 30 .
[0162] The paste for forming the conductive resin layer may include resin and conductive metal, and may optionally include non-conductive filler. Since the description of the conductive metal and the resin is the same as above, repeated description will be omitted. In addition, the paste for forming the conductive resin layer may optionally include an adhesive, a solvent, a dispersant, a plasticizer, an oxide powder, etc. The adhesive may be, for example, ethyl cellulose, acrylic acid, butyral, etc., and the solvent may be an organic solvent or an aqueous solvent, for example, terpineol, butyl carbitol, ethanol, methyl ethyl ketone, acetone, and toluene.
[0163] For example, the conductive resin layer may be formed by immersing the capacitor body 110 in a paste for forming the conductive resin layer and then curing it, or by printing the paste for forming the conductive resin layer on the surface of the capacitor body 110 by screen printing or gravure printing, or by applying the paste for forming the conductive resin layer to the surface of the capacitor body 110 and then curing it.
[0164] Next, a plating layer may be formed on the outer side of the conductive resin layer.
[0165] For example, the plated layer can be formed by a plating method, sputtering, or electrolytic plating (electrodeposition).
[0166] The above embodiments will be described in more detail by the following examples. However, the following examples are only for illustrative purposes and do not limit the scope of the appended claims.
[0167] (Manufacture of multilayer ceramic capacitors)
[0168] Example 1
[0169] After a dielectric green sheet is manufactured by using a main component powder of barium titanate (BaTiO3), a conductive paste layer including nickel (Ni) is printed on the surface of the dielectric green sheet, and the dielectric green sheets formed with the conductive paste layer are stacked and pressed to manufacture a dielectric green sheet stack (width×depth×height=3.2mm×2.5mm×2.5mm). The dielectric green sheet stack is plasticized at 400°C or lower in a nitrogen atmosphere, and then fired at a firing temperature of 1300°C or lower and a hydrogen concentration of 1.0% H2 or lower, thereby manufacturing a capacitor body.
[0170] The first paste for forming the lower layer (including Cu and a first glass composition containing the composition of Table 1 below) is applied to the surface of the capacitor body, and then sintered at 730°C for 1 hour to form the lower layer of the external electrode. Here, the amount of Cu is 90wt% relative to the total amount of Cu and the first glass composition, and the amount of the first glass composition is 10wt%. Subsequently, the second paste for forming the upper layer (including Cu and a second glass composition containing the composition of Table 1 below) is applied to the formed lower layer, and then sintered at 730°C for 1 hour to form the upper layer of the external electrode. Here, the amount of Cu is 90wt% relative to the total amount of Cu and the second glass composition, and the amount of the second glass composition is 10wt%. Subsequently, a multilayer ceramic capacitor is manufactured by a process such as plating.
[0171] (Table 1)
[0172] The unit is mole parts relative to 100 mole parts of the total amount of each of the first glass composition and the second glass composition.
[0173]
[0174] Comparative Example 1
[0175] A multilayer ceramic capacitor was manufactured in the same manner as in Example 1, except that a paste for forming an external electrode (including Cu and a glass composition having a composition of Table 2 below) was applied on the surface of the capacitor body and sintered at 730° C. for 1 hour to form the external electrode. Here, the amount of Cu was 90 wt %, and the amount of the glass composition was 10 wt %, relative to the total amount of Cu and the glass composition.
[0176] (Table 2)
[0177] The unit is mole parts relative to 100 mole parts of the total amount of the glass composition.
[0178]
[0179] Assessment 1: SEM analysis
[0180] The multilayer ceramic capacitor manufactured in Example 1 was subjected to scanning electron microscope (SEM) analysis, and the results are shown in FIG. Figure 5 middle.
[0181] SEM analysis is performed as follows. The multilayer ceramic capacitor 100 manufactured in Example 1 is placed in an epoxy resin mixture liquid and cured, and then polished by using sandpaper and diamond suspension to obtain a cross-sectional sample having an LT surface (cross section in the length direction and thickness direction) so that the external electrode can be observed. The obtained cross-sectional sample is measured by a scanning electron microscope (SEM). For example, the SEM measurement is performed by using Tescan's Vega3 under the conditions of 20kV, 0.2nA and 3k times magnification.
[0182] Figure 5 is a SEM analysis image of the external electrodes of the multilayer ceramic capacitor according to Example 1.
[0183] Reference Figure 5 , it can be confirmed that, in the case of Example 1 according to the embodiment, the external electrode is formed in a double-layer structure of a lower layer and an upper layer on the surface of the capacitor body.
[0184] Assessment 2: SEM-EDS analysis
[0185] The multilayer ceramic capacitor manufactured in Example 1 was subjected to scanning electron microscope-energy dispersive spectroscopy (SEM-EDS) analysis, and the results are shown in Fig. 6A and Figure 6B middle.
[0186] SEM-EDS analysis is performed as follows. The multilayer ceramic capacitor 100 manufactured in Example 1 is placed in an epoxy resin mixture liquid and cured, and then polished using sandpaper and diamond suspension to obtain a cross-sectional sample having an LT surface (cross section in the length direction and thickness direction) so that the external electrode can be observed. The obtained cross-sectional sample is measured by a scanning electron microscope (SEM). For example, the SEM measurement is performed under the conditions of 20kV, 0.2nA and 6005 times the magnification by using Tescan's Vega3. Subsequently, in the SEM image of the measured cross-sectional sample, the content of each component present in the lower layer and the upper layer of the external electrode is confirmed by performing energy dispersive spectrometer (EDS) analysis.
[0187] Fig. 6A is a cross-sectional SEM-EDS analysis image about the upper layer of the outer electrode according to Example 1. Figure 6B is a cross-sectional SEM-EDS analysis image about the lower layer of the outer electrode according to Example 1.
[0188] Reference Fig. 6A and Figure 6B , it can be seen that, in the case of Example 1 according to the embodiment, the first glass included in the lower layer of the external electrode includes aluminum (Al) in an amount of 7.64 atomic %, and the second glass included in the upper layer of the external electrode includes aluminum (Al) in an amount of 16.0 atomic %.
[0189] Assessment 3: SEM analysis
[0190] The multilayer ceramic capacitors manufactured in Example 1 and Comparative Example 1 were subjected to scanning electron microscope (SEM) analysis to measure the thickness of the external electrodes at the center and corners, and the results are shown in FIG. Fig. 7A and Figure 7B and Table 3 below.
[0191] SEM analysis was performed in the same manner as in Evaluation 1. In the obtained SEM image of the external electrodes, in the external electrodes 131 and 132, the portion disposed at the center point of the third surface and the fourth surface in the thickness direction (T-axis direction) is defined as a center portion A, and the portion disposed at the point where the three surfaces of the capacitor body 110 intersect is defined as a corner portion B.
[0192] Fig. 7A is a cross-sectional SEM-EDS analysis image of an external electrode of the multilayer ceramic capacitor according to Example 1. Figure 7B is a cross-sectional SEM-EDS analysis image of an outer electrode of the multilayer ceramic capacitor according to Comparative Example 1.
[0193] (Table 3)
[0194]
[0195] Refer to Table 3 and Fig. 7A and Figure 7B , it can be seen that, in the case of Example 1 according to the embodiment, compared with Comparative Example 1, the thickness at the corner portion of the external electrode increases.
[0196] Assessment 4: EPMA Analysis
[0197] The multilayer ceramic capacitor manufactured in Example 1 was subjected to electron probe microanalyzer (EPMA) analysis, and the results are shown in FIG. Figure 8 and Table 4 below.
[0198] EPMA analysis was performed as follows. The multilayer ceramic capacitor 100 manufactured in Example 1 was placed in an epoxy resin mixture liquid and cured, and then polished using sandpaper and diamond suspension to obtain a cross-sectional sample having an LT surface (cross section in the length direction and thickness direction) to be able to observe the external electrode. The obtained cross-sectional sample was subjected to an electron probe microanalyzer (EPMA) analysis under the conditions of a voltage of 15 kV and a magnification of 10 k. The measurement results, mapping, and content of each element present in the lower and upper layers of the external electrode were confirmed.
[0199] Figure 8 is a cross-sectional EPMA analysis image of an external electrode of the multilayer ceramic capacitor according to Example 1.
[0200] (Table 4)
[0201] The unit is atomic % relative to the total amount of components of the first glass and the total amount of components of the second glass, respectively.
[0202]
[0203] Refer to Table 4 and Figure 8 , it can be confirmed that, in the case of Example 1, sodium (Na) and iron (Fe) exist as main components in the second glass component included in the upper layer of the external electrode.
[0204] In addition, sodium (Na) and iron (Fe) detected in a small amount in the lower layer of the outer electrode are understood to be components derived from sodium oxide (Na2O) and iron oxide (Fe2O3) added when forming the upper layer of the outer electrode and diffused into the lower layer.
[0205] Evaluation 5: Moisture resistance reliability
[0206] The moisture resistance reliability of the multilayer ceramic capacitors manufactured in Example 1 and Comparative Example 1 was measured, and the results are shown in Fig. 9A and Fig. 9B middle.
[0207] In more detail, ten multilayer ceramic capacitors according to Example 1 and Comparative Example 1 were prepared respectively and mounted on a measurement substrate, and measured by using ESPEC (PR-3J, 8585) equipment under the conditions of 85°C, relative humidity (RH) 85%, 6.3V and 24 hours.
[0208] Fig. 9A is a graph showing the moisture resistance reliability regarding the external electrode according to Example 1. Fig. 9B is a graph showing the moisture resistance reliability of the external electrode according to Comparative Example 1.
[0209] Reference Fig. 9A and Fig. 9B, it can be seen that, compared with Comparative Example 1 in which the external electrode is formed in a single layer, in the case of Example 1 in which the external electrode according to the embodiment is formed in a double layer and Al is included in the lower layer and the upper layer at different atomic %, the moisture resistance reliability is excellent.
[0210] While the present disclosure has been described in connection with what are presently considered to be practical embodiments, it should be understood that the present disclosure is not limited to the disclosed embodiments, but on the contrary is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
Claims
1. A multilayer ceramic capacitor comprising: a capacitor body including a dielectric layer and an inner electrode layer; as well as An external electrode, disposed outside the capacitor body, wherein the outer electrode comprises a lower layer and an upper layer, the lower layer being located on the surface of the capacitor body to be electrically connected to the inner electrode layer, and the upper layer covering the lower layer, wherein the lower layer comprises a first glass, the first glass comprising Al in an amount greater than 0 atomic % and less than or equal to 8 atomic % relative to the total amount of components of the first glass, and The upper layer includes a second glass, and the second glass includes Al in an amount greater than or equal to 10 atomic % and less than or equal to 20 atomic % relative to the total amount of components of the second glass.
2. The multilayer ceramic capacitor according to claim 1, wherein An atomic ratio of an amount of Al included in the second glass to an amount of Al included in the first glass is greater than 2 and equal to or less than 100.
3. The multilayer ceramic capacitor according to claim 1, wherein The second glass also includes Li, Na, Fe, Ba, Ca, Zn, B, Si, Sn or a combination thereof.
4. The multilayer ceramic capacitor of claim 3, wherein: The second glass comprises Si; and The total composition of Al and Si is 20 atomic % to 50 atomic % relative to the total composition of the second glass.
5. The multilayer ceramic capacitor according to claim 1, wherein The first glass also includes Li, Na, Fe, Ba, Ca, Zn, B, Si, Sn or a combination thereof.
6. The multilayer ceramic capacitor of claim 5, wherein: The first glass includes Ba and Zn; and The total composition of Ba and Zn is 50 atomic % to 95 atomic % relative to the total composition of the first glass.
7. The multilayer ceramic capacitor of claim 1, wherein: The first glass and the second glass further include Na; and An atomic ratio of an amount of Na included in the second glass to an amount of Na included in the first glass is greater than 2 and 100 or less.
8. The multilayer ceramic capacitor of claim 1, wherein: The first glass and the second glass further include Fe; and An atomic ratio of an amount of Fe included in the second glass to an amount of Fe included in the first glass is greater than 2 and equal to or less than 100.
9. The multilayer ceramic capacitor according to claim 1, wherein: At least one of the lower layer and the upper layer further includes a conductive metal.
10. The multilayer ceramic capacitor according to claim 9, wherein The conductive metal includes Cu, Ni, Ag, Pd, Au, Pt, Sn, W, Ti, Pb, alloys thereof, or combinations thereof.
11. The multilayer ceramic capacitor according to claim 1, wherein The external electrode includes a central portion and a corner portion, the central portion includes a central point of the multilayer ceramic capacitor in a thickness direction, the corner portion includes a corner point of the multilayer ceramic capacitor, and a thickness ratio of the corner portion to the central portion of the external electrode is 0.1 to 0.
5.
12. The multilayer ceramic capacitor according to claim 3, wherein: The second glass includes Li.
13. The multilayer ceramic capacitor according to claim 12, wherein: The first glass further comprises Li, and An atomic ratio of an amount of Li included in the second glass to an amount of Li included in the first glass is greater than 1.
14. A method of manufacturing a multilayer ceramic capacitor, the method comprising: applying a first paste for forming a lower layer of an external electrode on a surface of a capacitor body, the capacitor body including a dielectric layer and an internal electrode layer, the lower layer including a first glass; forming the lower layer by sintering the first paste; applying a second paste for forming an upper layer of the external electrode on the lower layer, the upper layer comprising a second glass; and forming the upper layer by sintering the second paste, wherein the first paste includes a first glass composition that forms the first glass, and the first glass composition includes Al2O3 in an amount greater than 0 mol parts and less than or equal to 8 mol parts relative to 100 mol parts of the total amount of the first glass composition, and The second paste includes a second glass composition for forming the second glass, and the second glass composition includes Al2O3 in an amount greater than or equal to 10 mol parts and less than or equal to 20 mol parts relative to 100 mol parts of the total amount of the second glass composition.
15. A method of manufacturing a multilayer ceramic capacitor, the method comprising: applying a first paste for forming a lower layer of an external electrode on a surface of a capacitor body, the capacitor body including a dielectric layer and an internal electrode layer, the lower layer including a first glass; applying a second paste for forming an upper layer of the external electrode on the first paste, the upper layer including a second glass; and forming the external electrode including the lower layer and the upper layer by sintering the capacitor body coated with the first paste and the second paste, wherein the first paste includes a first glass composition that forms the first glass, and the first glass composition includes Al2O3 in an amount greater than 0 mol parts and less than or equal to 8 mol parts relative to 100 mol parts of the total amount of the first glass composition, and The second paste includes a second glass composition for forming the second glass, and the second glass composition includes Al2O3 in an amount greater than or equal to 10 mol parts and less than or equal to 20 mol parts relative to 100 mol parts of the total amount of the second glass composition.
16. The method for manufacturing a multilayer ceramic capacitor according to claim 14 or 15, wherein: The first glass composition further includes BaO, CaO, ZnO, B2O3, SiO2 or a combination thereof.
17. The method for manufacturing a multilayer ceramic capacitor according to claim 16, wherein: Relative to 100 parts by mole of the total amount of the first glass composition: The amount of BaO is 10 to 40 parts by mole; The amount of CaO is 1 to 20 parts by mole; The amount of ZnO is 10 to 40 parts by mole; The amount of B2O3 is 10 to 40 parts by mole; and The amount of SiO2 is 1 to 20 parts by mole.
18. The method for manufacturing a multilayer ceramic capacitor according to claim 14 or 15, wherein: The second glass composition further includes Li2O, Na2O, BaO, CaO, ZnO, B2O3, SiO2, Fe2O3 or a combination thereof.
19. The method for manufacturing a multilayer ceramic capacitor according to claim 18, wherein: Relative to 100 parts by mole of the total amount of the second glass composition: The amount of Li2O is 1 to 20 parts by mole; The amount of Na2O is 1 to 20 parts by mole; The amount of BaO is 10 to 40 parts by mole; The amount of CaO is 1 to 20 parts by mole; The amount of ZnO is 1 to 20 parts by mole; The amount of B2O3 is 10 to 40 parts by mole; The amount of SiO2 is 1 to 20 parts by mole; and The amount of Fe2O3 is 0.1 to 10 parts by mole.
20. The method for manufacturing a multilayer ceramic capacitor according to claim 14 or 15, wherein: At least one of the first paste and the second paste further includes a conductive metal.